LEGAL EDUCATION OF PHARMACISTS IN A CONTEXT OF SOCIETY DEMOCRATIZATION AND THE EUROPEAN STANDARDS OF EDUCATION IN UKRAINE - I. M. Alieksieieva (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
In order to determine the urgent need for scientific applied research to improve legal education and legal education in higher educational institutions of the pharmaceutical and medical profile conditions have been explored by such methods as observation, comparison, analysis and synthesis, identification, description and interpretation. It has been established that the main source of specific legal education must be current legislation and international instruments ratified by the Ukrainian parliament - the VerkhovnaRada, which is common tool of general civil and professional relationships regulation. This suggests that state government should strive to keep this professional category not only highly professional, but also highly moral, highly cultured and the right conscious.